Formation and implementation of regional land policy in Ukraine: public governance aspects. (Economics and region, 2020)
The article presents the concept of regional land policy formation. The concept is developed on the basis of basic theory of economic policy, public administration and taking into account the standards of sustainable development. The concept provides an opportunity to justify the directions, methods and instruments of regulation of land relations at the regional level. The subjects of regional land policy at the national and regional levels of government are highlighted. It is proved that regional land policy should be implemented by economic and administrative methods on the following principles: legality, inviolability of land ownership, inclusion of land in the market circulation, combination of economic efficiency and environmental safety of land use, payment, purpose of use, priority of national interests, differentiated land management of different categories and regions. With the help of the scale of relative advantages by T. Saati it is established that the stimulating type of implementation of land policy, which provides comprehensive assistance to the active development of market processes, is a priority for the Poltava region at the present stage of land relations.
Keywords: regional land policy; land policy priorities; policy implementation instruments; sustainable development; public management